The register of unscrupulous suppliers as a tool for protecting state interests and preventing violations in the procurement sphere - Zhagalov, R.B. (Karaganda National Research University named after àcademician Ye.A. Buketov, 2025)
The public procurement system represents a set of relationships directly linking state authorities and suppliers. Integrity and reliability of contracting parties serve as key guarantees of stability in civil turnover. This, in turn, is defined as the principal objective of the public procurement system, namely, the effective management of public finances and the state budget, as well as the protection of public interests. This article addresses both theoretical and practical issues of civil-law liability of unfair counterparties arising within the sphere of tender relations in Kazakhstan. The purpose of the study is to identify the scope of civil-law liability of unfair suppliers in public procurement, to strengthen this liability, to emphasize the significance of the Register of Unfair Suppliers, and to develop relevant legislative proposals. The research applies a comparative analysis of domestic and foreign legislation, supported by judicial practice, in order to achieve the stated objectives. The study also proposes the introduction of the concept of an “unfair supplier” into the Law of the Republic of Kazakhstan “On Public Procurement” and other normative acts, as well as the integration of registers of unfair suppliers across procurement-related platforms. The methodological framework of the study includes formal-logical, analytical and synthetic, comparative-legal, general-state, statistical, and historicallegal methods.
Жосықсыз өнім берушілердің тізілімі мемлекеттік мүдделерді қорғау және сатып алу саласындағы бұзушылықтардың алдын алу құралы ретінде
Реестр недобросовестных поставщиков как инструмент защиты государственных интересов и предотвращения нарушений в сфере закупок
Keywords: tender; public procurement; civil liability; unfairness; penalty; contracting authority; supplier; register; contract; portal